Technical approaches for enhancing thermal management of hybrid photovoltaic thermal systems: emerging trends and future prospects - Mukul Kant Paliwal; Sanjeev Jakhar; Arushi Dixit; Vikrant Sharma (International Journal of Thermofluids)
PV technology’s drawback is low efficiency due to its high surface temperature beyond 25 °C as compared to conventional power generation technologies. This article provides an analysis of advanced photovoltaic/thermal (PV/T) hybrid systems, focusing on the integration of cooling technologies including phase change materials (PCMs) and nanofluids systems. This study demonstrates that despite the lower efficiency of PV technology relative to conventional power generation, integrating water cooling with PCMs can significantly enhance performance, achieving thermal efficiencies of up to 86.19 % as per literature. Furthermore, PV/T Nano-PCM (nanoparticles used in PCM) technologies show potential, achieving electrical efficiency gains of up to 17.31 % and overall thermal conversion efficiencies reaching up to 19 % as per literature. The use of Sic nanofluids cooling technology for PV/T system is a significant innovation through which thermal efficiency and electrical efficiency increased by 100.19 % and 24.1 % respectively as compared to normal water cooling [49]. This paper presents a comprehensive analysis of novel cooling technologies, offering insights into the optimisation of PV/T systems to improve performance, and serves as a key resource for professionals in renewable energy research and development. It emphasises the innovative elements of the study, particularly the incorporation of nanofluids and PCMs, and their effect on enhancing system efficiency beyond that of conventional approaches.